After 25 Years as Faithful Members of the EU. Public Support for the Euro and Trust in the ECB in Austria, Finland and Sweden - Felix Roth; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2020)
Austria, Finland and Sweden became members of the EU in 1995. This paper examines how support for the euro and trust in the European Central Bank (ECB) have evolved in these three countries since their introduction at the turn of the century. Support for the euro in the two euro-area members Austria and Finland has remained high and relatively stable since the physical introduction of the new currency nearly 20 years ago, while the euro crisis significantly reduced support for the euro in Sweden. Since the start of the crisis, trust in the ECB was strongly influenced by the pronounced increase in unemployment in the euro area, demonstrating that the ECB was held accountable for macroeconomic developments. Our results indicate that citizens in the EU, both within and outside the euro area, judge the euro and the ECB based on the economic performance of the euro area. Thus, the best way to foster support for the euro and trust in the ECB is to pursue policies aimed at achieving low unemployment and high growth.
Keywords: E42; E52; E58; F33; F45; 330; euro; trust; ECB; EU; monetary union; Austria; Finland; Sweden